Reification of religious figures in azab genre religious sinetron: An interpretative phenomenological analysis - Haroni, Nanang; Arianti, Gusmia; Weaham, Muhammadroflee; Hamid, Abdul (Jurnal Ilmu Dakwah, 2024)
Purpose - To examine the phenomenon of reification in the presence of religious figures in Indonesian "azab" genre religious television series through the lens of Axel Honneth's theory of recognition. Method - This study employs an interpretative phenomenological analysis (IPA) and collects data through in-depth interviews with six informants (religious figures/actors, TV producers, directors, scriptwriters) involved in the production of "azab" genre religious television series. Results - This study indicates that individuals involved in the production of "azab" genre television series tend to neglect the antecedents of recognition—as per Honneth's concept of reification—such as the formation of identity and the role of media as a platform for da'wah. This neglect of recognition is influenced by interpersonal dynamics among workers and the market-driven pressures of the production environment. Implications -  This article offers a deeper understanding of the reality of the commodification of religion (Islam) and the perspectives of audiences who consume religious television, which is often positioned as a means of da'wah. Originality/Value - Theoretically, this article offers a new perspective on the dynamics and representation of religion (Islam) in the media. Through this, it is possible to develop academic critical strategies towards media and stakeholders who have a responsibility to improve religious broadcasting on television. *** Tujuan - Mengkaji fenomena reifikasi dalam kehadiran tokoh agama pada sinetron religi genre "azab" di Indonesia melalui lensa teori pengakuan Axel Honneth. Metode – Penelitian menggunakan metode Analisis Fenomenologi Interpretatif dan pengumpulan data melalui wawancara mendalam dengan enam informan (tokoh agama/pemain, produser TV, sutradara, penulis skenario) yang terlibat dalam produksi sinetron religi genre "azab." Hasil – Penelitian ini menunjukkan bahwa individu yang terlibat dalam produksi serial televisi bergenre "azab" cenderung melupakan pengakuan anteseden—seturut konsep reifikasi Axel Honneth-- terkait makna dan identitas diri,  juga tentang aspek lain seperti  media sebagai platform dakwah, serta peran tokoh agama di dalamnya. Kondisi melupakan pengakuan ini dipengaruhi dinamika interpersonal di antara pekerja dan tekanan lingkungan produksi yang digerakkan pasar. Implikasi – Artikel ini menyuguhkan kedalaman realitas pemaknaan isu-isu agama (Islam) dari perspektif pelaku industri sinetron religi yang secara umum diklaim sebagai sarana dakwah untuk melengkapi perspektif yang relatif populer dalam kajian media dan agama seperti komodifikasi. Orisinalitas/ Nilai – Artikel ini menampilkan cara pandang baru dalam melihat dinamika hubungan sekaligus representasi agama (Islam) di media. Melalui ini, dimungkinkan pengembangan strategi kritik akademik terhadap media dan stakeholder yang memiliki kaitan tanggungjawab dengan pentingnya memperbaiki siaran agama di televisi.